The cognitive bases of learning to read and spell in Greek: evidence from a longitudinal study. - Nikolopoulos, D; Goulandris, N; Hulme, C; Snowling, M (2006)
We conducted a longitudinal study examining the role of phonemic awareness, phonological processing, and grammatical skills in the development of reading and spelling abilities in Greek. A battery of cognitive, linguistic, and literacy tasks was administered to 131 primary school children (65 7-year-olds and 66 9-year-olds) and was repeated in the following year (8- and 10-year-olds, respectively). Phoneme awareness, speech rate, and rapid automatized naming (RAN) were concurrent predictors of reading rate at Time 1 (T1), and speech rate was a longitudinal predictor of reading rate at Time 2 (T2) when reading at T1 was controlled. The predictors of spelling differed from those of reading; phoneme awareness and speech rate predicted concurrent attainments at T1, and phoneme awareness was a robust longitudinal predictor. Despite the differences in the degree of transparency between the Greek and English orthographies, phoneme awareness predicts variations in learning to read and spell in both languages.